A death in the small hours - Finch, Charles (Charles B.) (Finch, Charles (Charles B.) Charles Lenox series., 2012)
Visiting his uncle's estate in Somerset for what he hopes will be a quiet working vacation, politician and new father Charles Lenox investigates a series of seemingly small acts of vandalism only to uncover a sinister plot by an adversary who may be targeting someone Lenox loves.